Lectura recomendada "Hacia la conquista de un pensamiento propio", autores: el niño y la niña - Cely Quintero, Adriana Esperanza; Espinosa Escobar, Ingrid Isabel (Universidad Pedagógica y Tecnológica de Colombia, 2016)
51 hojas